Pancreas Transplantation With Enteroanastomosis to Native Duodenum Poses Technical Challenges—But Offers Improved Endoscopic Access for Scheduled Biopsies and Therapeutic Interventions. Issue 1 (13th November 2014) - Horneland, R.; Paulsen, V.; Lindahl, J. P.; Grzyb, K.; Eide, T. J.; Lundin, K.; Aabakken, L.; Jenssen, T.; Aandahl, E. M.; Foss, A.; Øyen, O.
Abstract To facilitate endoscopic access for rejection surveillance and stenting of the pancreas, we have abandoned the duodenojejunostomy (DJ) in favor of duodenoduodenostomy (DD) in pancreas transplantation (PTx). From September 2012 to September 2013 we performed 40 PTx with DD; 20 solitary‐PTx (S‐PTx) and 20 simultaneous pancreas and kidney transplantation (SPK). We compared the outcomes with results from 40 PTx‐DJ (10 S‐PTx and 30 SPK) from the preceding era. The DD‐enteroanastomoses were performed successfully. Endoscopic pancreas biopsies (endoscopic ultrasound examination [EUS]) yielded representative material in half of the cases. One exocrine fistula was treated by endoscopic stenting. PTxs‐DD were associated with a higher rate of thrombosis compared to PTx‐DJ (23% vs. 5%) and reoperations (48% vs. 30%), as well as inferior graft survival (80% vs. 88%). Time on waiting list, HLA A + B mismatches and reoperations were associated with graft loss. Only recipient age remained an independent predictor of patient death in multivariate analysis. PTx‐DD showed a higher rate of thrombosis and inferior results, but facilitated a protocol biopsy program by EUS that was feasible and safe. Given that technical difficulties can be solved, the improved endoscopic access might confer long‐term benefits, yet this remains to be proven.